Educators' and learners' perceptions of paper 1 assessments in grade 10 Tshivenda Home Language at Elim Circuit, Vhembe District, Limpopo Province, South Africa - Nethononda, Ronewa Tracey (My University, 2025)
The purpose of this study was to investigate educators' and learners’ perceptions of Grade 10 Tshivenda Home Language Paper 1 assessment tasks at Elim Circuit, Vhembe West District, Limpopo Province, South Africa. The study used a qualitative approach to elicit observations and interviews from a sample of ten learners and two educators. The study is reinforced by the behaviourist learning theory. This study's research methodology was outlined within the framework of a qualitative research approach, guided by the interpretivism paradigm, and employing a case study design. The participants were selected using a simple random sampling. The researcher collected data by using semi structured interviews, non-participant observation, document review. The data was analysed using the thematic analysis method. The results of this study indicate that both educators and learners perceive Paper 1 assessment tasks, particularly those related to language structure and conventions, as challenging. The research identified several factors that contribute to the subpar performance in these areas, including laziness or ignorance, inadequate professional development for educators (such as workshops), the use of various authors in the textbooks of both learners and educators, a lack of sufficient teaching and learning materials, insufficient time allocation, limited exposure to language structure and conventions, and the attitudes of both educators and learners towards the Home Language. The analysis revealed that these factors hinder the quality of productive teaching and learning environment, and contribute to poor performance, and incorrect use of Tshivenda Home Language. Several recommendations are made to minimise learners’ poor performance in paper 1 assessment tasks such as libraries should be fully functional at schools and finally time allocation needs to be revised.
Thesis (M. Ed. (Language of Education)) -- University of Limpopo, 2025
Keywords: Language structure and convention; Assessment; Grammar; Behaviourist learning theory; Venda language -- Study and teaching; Venda language Grammar; Learning, Psychology of; Grammar, Comparative and general; Education, Secondary -- South Africa -- Limpopo